Prokrastinasi Akademik pada Siswa SMA: Peran Efikasi Diri dan Konformitas Teman Sebaya - Uswidatul Laili; Suhadianto; Herlan Pratikto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract The purpose of this study is to test the relationship between academic self-efficacy and peer conformity with academic procrastination among high school students. A quantitative approach with a correlational design was used. The participants were 305 students from a senior high school in Krian selected through stratified random sampling. The instruments applied concist of the academic self-efficacy scale, peer conformity scale, and academic procrastination scale. Multiple linear regression applied as data analysis. The results revealed a significant relationship between academic self-efficacy and peer conformity with academic procrastination. Academic self-efficacy showed a positive influence on procrastination, indicating that students with higher academic self-efficacy tend to delay academic tasks more frequently. Similarly, peer conformity also had a positive impact on academic procrastination. In conclusion, both variables contribute to procrastination behavior, highlighting the importance of increasing students' self-awareness and ability to manage social influence from their peers. Keywords: academic self-efficacy, peer conformity, academic procrastination, high school students, multiple linear regression Abstrak Tujuan penelitian ini adalah untuk mengujii hubungan antara efikasi diri akademik dan konformitas teman sebaya dengan prokrastinasi akademik Siswa SMA. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Subjek penelitian adalah 305 siswa SMA di Krian yang dipilih melalui teknik stratified random sampling. Instrumen yang diterapkan terdiri dari skala efikasi diri akademik, skala konformitas teman sebaya, dan skala prokrastinasi akademik. Regresi linier berganda diterapkan sebagai analisis data. temuan penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara efikasi diri akademik dan konformitas teman sebaya dengan prokrastinasi akademik. Efikasi diri akademik berpengaruh positif terhadap prokrastinasi akademik, yang berarti semakin tinggi efikasi diri akademik siswa, maka semakin tinggi pula kecenderungan untuk menunda tugas akademik. Selain itu, konformitas teman sebaya juga berpengaruh positif terhadap prokrastinasi akademik. Kesimpulan dari penelitian ini adalah bahwa kedua faktor tersebut berkontribusi terhadap perilaku menunda tugas, sehingga perlu adanya upaya untuk meningkatkan kesadaran diri siswa dan kemampuan memilah pengaruh sosial dari lingkungan sekitarnya. Kata kunci: efikasi diri akademik, konformitas teman sebaya, prokrastinasi akademik, siswa SMA, regresi linear berganda